EFL Teachers’ Pedagogical Practices based on Their Perception during Covid-19 Pandemic - Tanjung, Faisal (Center of Language and Cultural Studies [CLCS], 2022)
Abstract The objectives of this research were to explored the English teacher’s pedagogical practices in teaching English to the students and to find how great the influence of the English teacher’s pedagogical practices to the students learning achievement. In addition, this research was conducted through qualitative approach. The data of this research were taken from 7 EFL Teachers of Tinombo District. In collecting the data of this research, the researcher used interview and document analysis instrument to the students. The interviews are aimed at getting information directly about everything that relation with teacher competence and teacher in teaching learning process. Thus, the document analysis are aimed to complete information obtained through interview.Then, after analyzing the data obtained, it was concluded that the EFL teachers’ pedagogical practices of Tinombo district during pandemic Covid 19 as a whole were using teaching methods and strategies that were tailored to the needs and abilities of students, giving various kinds of tests and assignments to students to find out the extent of student understanding, understanding students' conditions by adjusting the teaching and learning process based on the developing situation in this case COVID-19, using media supporting the teaching process, assisting students in developing their potential and creativity, making good communication with students in the classroom, conducting assessments and evaluations using various techniques that are in accordance with learning materials and learning objectives, utilizing information on student learning outcomes as a reference for preparing learning designs , and using applications that support appropriate teaching strategies during the COVID-19 situation. In addition, The main problems of teachers in apply Pedagogical Practices to the Students during Covid 19 Pandemic were the unstable internet network connection in that area and the concentration of students in learning decreases.